2020
DOI: 10.3389/fpubh.2020.575330
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Central Nervous System Disease: A Review of the Impact of Fine Particulate Matter on Neurological Disorders

Abstract: Background: It is widely known that the harmful effects of fine dust can cause various diseases. Research on the correlation between fine dust and health has been mainly focused on lung and cardiovascular diseases. By contrast, the effects of air pollution on the central nervous system (CNS) are not broadly recognized.Findings: Air pollution can cause diverse neurological disorders as the result of inflammation of the nervous system, oxidative stress, activation of microglial cells, protein condensation, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(71 citation statements)
references
References 107 publications
1
50
1
1
Order By: Relevance
“…The link of inflammation to neuronal damage is evident from numerous reports. Some of the major toxic compounds in cigarette smoke are especially well known to cause systemic and cardiovascular inflammation (Figure 3), which also holds true for the brain, as reported for particulate matter [152,168], heavy/transition metal ions [169,170], reactive aldehydes [171,172], and volatile organic compounds [173,174]. The following experimental animal studies support inflammation-mediated neuronal damage that may contribute to aforementioned neuropsychiatric disease in smokers.…”
Section: Smoking and Brain Changes Affecting Neuropsychiatric Pathophysiologysupporting
confidence: 69%
“…The link of inflammation to neuronal damage is evident from numerous reports. Some of the major toxic compounds in cigarette smoke are especially well known to cause systemic and cardiovascular inflammation (Figure 3), which also holds true for the brain, as reported for particulate matter [152,168], heavy/transition metal ions [169,170], reactive aldehydes [171,172], and volatile organic compounds [173,174]. The following experimental animal studies support inflammation-mediated neuronal damage that may contribute to aforementioned neuropsychiatric disease in smokers.…”
Section: Smoking and Brain Changes Affecting Neuropsychiatric Pathophysiologysupporting
confidence: 69%
“…Autonomic imbalance is not just associated with cardiovascular disease, but with myriad CNS disorders such as Parkinson's Disease (Haapaniemi et al, 2001), Fragile X syndrome (Boccia and Roberts, 2000), and depression (Agelink et al, 2001). Furthermore, recent studies suggested that air pollution, including SHS, is linked to CNS disorders and neurodegenerative diseases (Calderon-Garciduenas et al, 2015;Vani et al, 2015;Kim et al, 2020;Shabani, 2021). Reducing SHS exposure in non-smokers with smoke-free policies in public venues could have a broader benefit to public health beyond pulmonary and cardiovascular consequences.…”
Section: Perspectivementioning
confidence: 99%
“…Damage to neuronal cells caused by fine dust, especially in fetuses and infants, can cause permanent brain damage or lead to neurological disease in adulthood. Epidemiological studies have reported that the risk of developing dementia and Alzheimer's disease is increased by exposure to fine particulates (60).…”
Section: Toxicity Mechanisms Of Air Pollutionmentioning
confidence: 99%
“…There are many mechanisms through which air pollutants may cause pathologies in the nervous system, such as nervous system inflammation, oxidative stress, microglial cell activation, protein condensation, and cerebral vascular barrier disorders, but how these mechanisms occur is still unclear (60). The main components of air pollution, PM2.5, as well as the compounds absorbed on their surfaces arrest cell cycles and cause neural apoptosis.…”
Section: Toxicity Mechanisms Of Air Pollutionmentioning
confidence: 99%